Hypovitaminosis D Is Prevalent in Patients With Renal AL Amyloidosis and Associated With Renal Outcome - Muchtar, Eli; Drake, Matthew T.; Leung, Nelson; Dispenzieri, Angela; Lacy, Martha Q.; Buadi, Francis K.; Dingli, David; Hayman, Suzanne R.; Kapoor, Prashant; Hwa, Yi Lisa; Fonder, Amie; Hobbs, Miriam; et al. (Frontiers in Endocrinology, 2022)
Introduction: Vitamin D deficiency is common, but no data have been reported on vitamin D levels in light chain (AL) amyloidosis. Patients and Methods: In this exploratory study, stored serum samples from 173 patients with newly diagnosed AL amyloidosis were analyzed for vitamin studies included 25-hydroxyvitamin D [25(OH)D], 1,25-dihydroxyvitamin D [1,25(OH)2D] and vitamin D binding protein (DBP). Measurements were made by liquid chromatography-tandem mass spectrometry. Kidney survival and overall survival (OS) were assessed in association to vitamin D status. Results: Cardiac and kidney involvement occurred in 69% and 63% of patients, respectively. 25(OH)D deficiency (<20 ng/mL) was seen in 56.6% of the patients and was notably found among patients with heavy proteinuria (96%), hypoalbuminemia (84.3%) and morbidly obese patients (68.3%). Heavy proteinuria (>5 gr/24-h) and vitamin D supplementation were independent predictors of 25(OH)D deficiency on nominal multivariate regression analysis. 1,25(0H)2D deficiency was noted in 37.6% of patients and was independently associated with low eGFR and hypoalbuminemia. Progression to ESRD occurred in 23.7% of evaluable patients. Patients who progressed to ESRD had lower serum 25(OH)D and 1,25(OH)2D levels compared to those who did not progress to ESRD. On a multivariate analysis, severe 25(OH)D deficiency was an independent predictor of progression to ESRD as was renal stage, while 1,25(OH)2D deficiency was not. Patients with 25(OH)D levels >20 ng/mL had shorter OS compared to patients with lower 25(OH)D values (median 31.1 vs 49.2 months; P=0.03). Conclusions: Hypovitaminosis D is common in AL amyloidosis, particularly among patients with heavy proteinuria. Severe 25(OH)D deficiency at time of diagnosis predicts progression to ESRD.